ANALISIS SEBARAN SEDIMEN BERDASARKAN UKURAN BUTIR DAN NILAI SORTASI DI PERAIRAN PULAU DUTUNGAN KABUPATEN BARRU SULAWESI SELATAN - Hasriyanti Hasriyanti (Teknosains, 2015)
This study aims to determine the distribution of sediments basedon the type of grain and sorting values in the waters of the island DutunganBarru. Seabed sediment sampling was also carried out by using a bottomgrab samples were performed at each station. Note the position and timepengamatan.Sampel drawn on the bottom sediment grab samples insertedinto the sediment sample bag and labeled. Laboratory analysis to determinethe type, grain size / diameter of the bottom waters. Field data collectionactivities carried out at 12 sampling points, but there are two points that didnot work because the bottom waters sampled in the form of hard coral,making it very difficult for the presence of basic sediment samples waters.The results showed that the characteristics of the sediment on the islandconsists of silt Dutungan greatest on Observation Station 4 with a value of0.09 grams sorting medium, very fine sand to the largest measurementstation 8 at 8.20 grams with sorting pretty good value, fine sand onmeasurement station 9 at 56.02 grams with sorting value ugly, sand is beinggreatest at Observation Station 1 at 58.28 grams with sorting pretty goodvalue, most large coarse sand on Observation Station 5 at 54.11 grams witha very good value, very coarse sand greatest at 8 Observation Station at21.84 grams with sorting pretty good value, and most large gravel onObservation Station 7 of 63.5 grams with moderate sorting value. On theMeasurement Station 1 is dominated by sand sediment medium (0.25 to 0.85mm) although containing fine sand (0.15 to 0.25 mm) and silt (<0.15 mm)higher than the measurement station other. This is due to its location furtheraway from the beach and sheltered from the effects of ocean waves and thenumber of organic matter and detritus that brought water to accumulate inthe waters of this river, especially at lower currents.